Dampak Auditor Switching dan Financial Distress terhadap Audit Delay dengan Reputasi KAP sebagai Moderasi (Studi Empiris pada Perusahaan Properti & Real Estate, 2021-2023) - Julita Nia, Diana; Riswan, Riswan (Journal of Accounting and Finance Management, 2025)
This study reveals the impact of auditor switching and financial distress on audit delay, with Public Accounting Firm (PAF) Reputation as a moderating variable. The research utilizes secondary data obtained from financial reports published by the Indonesia Stock Exchange (IDX) in the property and real estate sector for the years 2021-2023. Sampling was conducted using a purposive sampling method, with multiple linear regression analysis and data processing performed using SPSS. The findings indicate that auditor switching has a positive effect on audit delay, financial distress has a negative effect on audit delay, and the moderating variable, PAF reputation, successfully acts as a moderator in the relationship between auditor switching, financial distress, and audit delay.